Visual Basic 2012 Programmer's Reference - Stephens, Rod (John Wiley & Sons, Incorporated, 2012)
Rod Stephens is a VB programming guru and the author of more than two dozen programming books, including Stephens' Visual Basic Programming 24-Hour Trainer. He also writes frequently for such magazines as Visual Basic Developer, Visual Basic Programmer's Journal, and Dr. Dobb's Journal. Rod's VB Helper website (vb-helper.com) provides thousands of pages of tips, tricks, and code examples for VB programmers